Desenvolvimento e caracterização de aguardente de frutas a base de polpa de banana (Musa sp.) e de suco de abacaxi (Ananas comusus (L) Merril) - Moro, Karine Ines Bolson (2016)
Brazil is the third biggest fruit producer in the world, condition that make the orcharding sector one of the most important economic activities, and generating of employment income, and providing rural development. However, part of this production is wasted every year increasing thereby the fruit waste rates a reason that just part of the production arrives to the consumer. Therefore, the industrialization represents an option of the utilization of the surplus of production of fruits and the non standard to consume in natura as well. The production of fruit brandy has found some problems because of the high level of higher alcohols formation and methanol during the fermentation. The fermentation broth conditions and the fermentation temperature may be contributing to the formation of these compounds. Grounded on such information this research aimed use the banana on its last stage of maturation, use its pulp, and use pineapple juice in the elaboration of fruit brandy as option of utilization avoiding this waste, aggregating value and contributing to the local development of a high value product. In this study was produced a banana (cv. Prata) brandy with banana pulp and banana (cv. Prata) pulp with pineapple (cv. Perola) juice brandy in a proportion of 2:1 (v/w) respectively. The fermentation broths were passed per the enzymatic hydrolyze process and also was added the polygalacturonase enzyme at a concentration of 170 μg mL-1 of broth. After two hours of enzymatic action the broths were centrifuged at 12.000 ×g during five minutes. The broths were inoculated with Saccharomyces cerevisiae (FX5) and the fermentation process occurred at a 16 ± 1 °C temperature. The fermented broths were distillated using a copper distiller and the produced brandies were stored in amber flasks and kept resting during 30 and 60 days. The volatile compounds were determined with a gas chromatograph with ionization detector in flame CG/FID. In between the produced brandies the best results were accomplished with the banana with pineapple juice brandy. Both produced brandies kept the standards of the Brazilian law of fruit brandies except just of the methanol level likely, because of the pectin degradation contained at the banana pulp. Evidencing that the fermentation broth conditions and the fermentation temperature are linked with the levels of the higher alcohols contained in the beverages. The higher alcohols levels varied from 298.12 to 197.11 mg 100 mL-1 of anhydrous alcohol (AA) for banana brandy during 30 and 60 days of rest respectively. The mix of banana pulp with pineapple brandy higher alcohols levels varied from 282.66 to 268.14 mg 100 mL-1 of AA during the 30 and 60 days of rest respectively. Therefore, it is proven the feasibility of fruit use to produce brandies and contributing to the developing of the agribusiness, and aggregating value to the products but more studies are required to decrease the high level of methanol found in this study.